Application of Mutated Acetolactate Synthase Genes for Herbicide Resistance to Crop Improvement - Shimizu, Masanori; Kawai, Kiyoshi; Kaku, Koichiro; Shimizu, Tsutomu; Kobayashi, Hirokazu (IntechOpen, 2011)
None